Perilaku Ibu Dalam Pencegahan Penyakit Demam Berdarah Dengue (DBD) Pada Balita Di Kelurahan Belawan Bahagia Kecamatan Medan Belawan - Nixson Manurung (Jurnal Penelitian Keperawatan Medik, 2020)
Dengue Hemorrhagic Fever (DHF) is a disease that is still the center of attention because the number of cases is increasing in number of cases in children under five. Some of the factors that are thought to influence are behavioral factors in the form of behavioral domains, namely knowledge, attitudes and practices in the implementation of prevention for housewives and their families. The purpose of this study was to identify the relationship between maternal knowledge and attitudes in the prevention of Dengue Hemorrhagic Fever (DHF) in toddlers. This type of research uses the type of research that is analytic observation with a cross sectional research design. The total sampling used in this study were 32 mothers who had children under five in Sido Rukun village who had toddlers. The data measurement technique was carried out by the researcher using a closed questionnaire to the respondents as many as 24 questions, namely, 12 questions for Independent Variables and 12 questions for Dependent Variable questions. The results showed that out of 32 mothers who became respondents, it was shown that the knowledge of mothers about Dengue Hemorrhagic Fever (DHF) was still quite good, namely 18 respondents (56.3%). Based on the attitude of the results found by the researcher, the majority of 32 mothers who had toddlers had good attitudes as many as 19 respondents (59.4%). The results of the analysis by researchers that have been carried out show that there is a relationship between maternal knowledge and attitudes in the prevention of dengue hemorrhagic fever (DHF), this can be seen from statistical tests using SPSS using the dhisquare test, analysis p = 0.03 means p <0.05 the results of the distribution and the questionnaire sheets that were distributed to the respondents. The conclusion is that there is a relationship between maternal knowledge in determining maternal attitudes towards the prevention of Dengue Hemorrhagic Fever (DHF) in toddlers.